Diurnal and seasonal variations of the occurrence of ionospheric irregularities over Nigeria from GNSS data - Ikani, Ojochenemi; Okeke, Francisca Nneka; Okpala, Kingsley Chukwudi; Okoh, Daniel; Rabiu, Babatunde (Frontiers in Astronomy and Space Sciences, 2023)
We investigate the occurrence of ionospheric irregularities in Nigeria during 2014, using the Global Navigation Satellite System (GNSS) total electron content (TEC) rate of change index (ROTI). We categorized days with |Dst| < 30 nT as quiet days and days with |Dst| ≥ 50 nT as disturbed days, during both the daytime and nighttime periods. Our results reveal significant latitudinal differences in both quiet and disturbed conditions. The quiet-time observations indicate that irregularities were consistent across all the stations. The occurrence was strong and consistent at CLBR station in Calabar, Nigeria, which is located further away from the geomagnetic equator (and closer to the southern anomaly crest) than the other receivers. TEC variability is greatly influenced by the geographical location of the Earth's magnetic field, while its spatial patterns of variability are modulated by the Earth's diurnal rotation. Near the September equinox, the occurrence of irregularities was inhibited during disturbed periods, but 2 an opposite pattern was observed during the March equinox across all stations. Two peaks of occurrence were observed: one in March and the other in September respectively. The strength of irregularities was generally greater in March equinox compared to September equinox, and they were more pronounced during pre-midnight hours. This pattern could be attributed to the suppressing role of the dynamo electric field, requiring further investigation.